First molecular identification of Cryptosporidium by 18S rRNA in goats and association with farm management in Terengganu - Mat Yusof, Afzan; Hashim, Najat; Md Isa, Muhammad Lokman (Wolters Kluwer Medknow Publications, 2017)
Objective: To identify the prevalence of Cryptosporidium from goats in three types of farm management systems in Terengganu, Malaysia and to determine the Cryptosporidium species infecting goats by using 18S rRNA. Methods: A total of 478 fecal samples were randomly collected from goats in three farms; 199 samples were collected from intensive farm, 179 samples from semi-intensive farm and 100 samples from extensive farm. The samples were processed by using formolether concentration technique and stained by using modified Ziehl–Neelsen. Positive samples were performed by using nested PCR analysis by using 18S rRNA. Results: Out of 478 goats, 207 (43.3%) were found to be infected with Cryptosporidium. Goats reared under the intensive farm management system reported the highest prevalence of infection (49.7%), followed by intensive farm management system (41%) and the lowest prevalence was reported in the goats reared under semi-intensive management system (37.4%). Conclusions: The identified species found in goat was Cryptosporidium parvum. Future study on the zoonotic transmission of Cryptosporidium parvum in goats needs to be done in order to find the source of transmission of this parasite.